2007
DOI: 10.1097/01.nmd.0000254748.38784.2f
|View full text |Cite
|
Sign up to set email alerts
|

The Subjective Experience of Trauma and Subsequent PTSD in a Sample of Undocumented Immigrants

Abstract: Although a subjective component of trauma is commonly recognized in diagnosing posttraumatic stress disorder (PTSD), there are few studies that specifically address Criterion A2, and none addressing this issue among undocumented immigrants. We assessed 212 arriving undocumented immigrants with diverse trauma histories to investigate concordance between objective and subjective factors of trauma (Criteria A1 and A2) and across different types of trauma and PTSD. Concordance between Criteria A1 and A2 varied, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 34 publications
1
32
2
2
Order By: Relevance
“…On the one hand, our results showed that possible PTSD diagnoses were associated with highly traumatic events like sexual assault and combat. This finding is consistent with studies revealing a high prevalence of PTSD diagnoses following events involving interpersonal violence, a violation of safety and social stigma (Rasmussen, Rosenfeld, Reeves, & Keller, 2007). On the other hand, and in agreement with other studies (Boals & Schuettler, 2009;Breslau et al, 1998;Peirce et al, 2009), we found that death or illness of a loved one were among the most frequently endorsed events and most often chosen as the index event.…”
Section: Part 2 Discussionsupporting
confidence: 93%
“…On the one hand, our results showed that possible PTSD diagnoses were associated with highly traumatic events like sexual assault and combat. This finding is consistent with studies revealing a high prevalence of PTSD diagnoses following events involving interpersonal violence, a violation of safety and social stigma (Rasmussen, Rosenfeld, Reeves, & Keller, 2007). On the other hand, and in agreement with other studies (Boals & Schuettler, 2009;Breslau et al, 1998;Peirce et al, 2009), we found that death or illness of a loved one were among the most frequently endorsed events and most often chosen as the index event.…”
Section: Part 2 Discussionsupporting
confidence: 93%
“…People who migrated between the ages of 12 and 17 years had higher risk for psychological disorders compared with the risk among Dutch citizens. However, the present study finding was inconsistent with previous studies of Ostrovschi et al [34] and Rasmussen et al [78].…”
Section: Discussioncontrasting
confidence: 57%
“…Researchers have shown that mental health problems particularly mental health distress and somatic complaints affect women to a greater extent than men across diverse societies and social contexts [40,77,78]. Pressures created by their multiple role and responsibilities, and associated factors such as gender based violence; contribute to women's poor mental health [10].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one study reported prevalence of alcohol/substance use as measured by the Alcohol Use Identification Test (AUDIT) among UIs before migration (90 days prior to migration), which may not accurately reflect current use (Dillon, De La Rosa, Sanchez, & Schwartz, 2012). Lastly, one study explored prevalence and predictors of PTSD among UIs at their point of entry to the United States and found that 11% of UIs met criteria for PTSD as measured by the Harvard Trauma Questionnaire, with at least 82% of participants reporting having experienced previous trauma (Rasmussen, Rosenfeld, Reeves, & Keller, 2007). Being a woman (OR D 2.3, 95% CI D 1.0, 6.2), having had exposure to violence by authorities (OR D 10.4, 95% CI D 1.1, 97.4) and domestic partners (OR D 26.0, 95% CI D 1.84, 367.7), and having had multiple traumas experienced as distressing (OR D 1.17, 95% CI D 1.0, 1.3) were associated with PTSD diagnosis.…”
Section: Findings From Quantitative Studies: Mental Health Outcomes Amentioning
confidence: 97%